Role of Leguminosae Root Fermentation on Vegetative Growth of Cayenne Pepper (Capsicum frutescens L.) after Flooding Stress - Hesti Kurniahu; Muhammad Rizza Pahlevi; Riska Andriani (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Flooded cayenne pepper (Capsicum frutescens L.) experiences oxidative stress causing growth disturbances, delayed and reduced yields, and even death. The success of cayenne pepper in the recovery process determines the overall success of cayenne cultivation after flooding stress. Leguminosae roots are associated with rhizosphere bacteria which are beneficial for the recovery process of cayenne pepper after flooding stress. This research used a Completely Randomized Design (CRD) with 5 treatments, namely T1 cayenne pepper without flooding and biofertilizer, T2 cayenne peppers without flooding and biofertilizer applied, T3 cayenne peppers flooded without biofertilizer application, T4 cayenne peppers flooded and 50% biofertilizer applied, T5 cayenne peppers flooded and 100% biofertilizer applied. Partial flooding was carried out for 48 hours and biofertilizer application was carried out after 24 hours of drainage. The results showed that the application of biofertilizer had a significant effect on the vegetative growth of cayenne pepper after flooding stress on the parameter of average number of leaves when applying 100% biofertilizer. This research concludes that Leguminosae root fermentation plays a role in the vegetative growth of cayenne pepper after flooding stress, so it has the potential to be used as a biofertilizer